Влияние количества наполнителя на качество отверстий при сверлении композитов - Хавин, Геннадий Львович; Есып, Инна Олеговна (НТУ "ХПИ", 2015)
Рассмотрено влияние количества наполнителя на шероховатость и расслоение в отверстиях при сверлении многослойных композиционных материалов. Представлен анализ экспериментальных и теоретических исследований образования расслоения и шероховатости в заготовке при сверлении. Описан механизм появления таких дефектов и современное состояние проблемы прогнозирования их количественных характеристик. Проанализировано влияние различных технологических факторов на уменьшение величины дефектов.

The influence of quantity of fill material on holes roughness and delamination when drilling of multilayer composite materials are considered. The analysis of experimental and theoretical studies of delamination and roughness in the workpiece during drilling is represented. The mechanism of occurrence of such defects and the current state of the problem of predicting their quantitative characteristics is described. The influence of different technological parameters on the reduction in the amount of defects, including delamination factor is analyzed.
The influense of quantity of fill material on holes quality when drilling composite materials
Keywords: дефект; композиты слоистые; шероховатость; drilling defects; layered composites; roughness during drilling